„Dzień przedsiębiorczości” - szansą na lepsze przygotowanie uczniów szkół ponadgimnazjalnych do wejścia na rynek pracy - Mrożek, Joanna (Przedsiębiorczość - Edukacja, 2008)
The following paper presents a Job Shadow Day undertaken by the Junior AchievementFoundation, a non-governmental organization with the aim of preparing children and youthsto live in market economy and to allow young people to gain knowledge and practical capabili-ties that facilitate the realization of the plans for career.The Foundation works within the framework of Junior Achievement Worldwide the oldestand fastest developing organization in the world, which is engaged in youth economic educationin more than one hundred countries. Junior Achievement Foundation pursues its objectivesin cooperation with the business environment, the Ministry of National Education and the Natio-nal Bank of Poland.Job Shadow Day allows young people to see in detail what the ideal job looks like, to learnabout its specifics, to find out about the required qualifications and indispensable skills. Suchan experience makes it possible to compare visions with reality and to have a better idea of the fu-ture job.